2018
DOI: 10.1080/10538712.2018.1501786
|View full text |Cite
|
Sign up to set email alerts
|

Prosecution of Child Sexual Abuse Cases Involving Preschool-Aged Children: A Study of Swedish Cases from 2010 to 2014

Abstract: Alleged child sexual abuse against preschool-aged children is often considered one of the most challenging cases for a prosecutor to handle. The aim of the current study was to examine differences between prosecuted and discontinued cases of alleged sexual abuse of preschool-aged children. Data from Swedish criminal cases of alleged sexual abuse of children ages 2-6 issued from 2010 to 2014 were analyzed (N = 130). Prosecuted cases were more likely to contain forensic evidence (documentation of abuse, corrobor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
4
14
1
Order By: Relevance
“…Our findings regarding the prosecuted CSA case features are in line with previous studies in jurisdictions from Western countries, such as the United States (Cross et al, 2003;Stolzenberg, & Lyon, 2015), Sweden (Diesen & Diesen, 2013;Ernberg et al, 2018), and Australia (Bunting, 2008;Christensen et al, 2016;Fitzgerald, 2006). First, cases in which there was a medicolegal report with a positive result were more likely to be prosecuted than those without a medicolegal report or with a negative medicolegal result.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our findings regarding the prosecuted CSA case features are in line with previous studies in jurisdictions from Western countries, such as the United States (Cross et al, 2003;Stolzenberg, & Lyon, 2015), Sweden (Diesen & Diesen, 2013;Ernberg et al, 2018), and Australia (Bunting, 2008;Christensen et al, 2016;Fitzgerald, 2006). First, cases in which there was a medicolegal report with a positive result were more likely to be prosecuted than those without a medicolegal report or with a negative medicolegal result.…”
Section: Discussionsupporting
confidence: 91%
“…Bunting (2008) found that cases with younger children were more likely to be dropped than cases with older children because they were considered too young to be a credible witness. Ernberg et al (2018) also noted in their study of pre-school aged children (range = 2-6 years, M= 4.52, SD = 1.25) that CSA cases with older pre-school children as alleged victims were more likely to be prosecuted than cases with younger pre-school children.…”
mentioning
confidence: 88%
See 3 more Smart Citations